First record of Celaenorrhinus ratna daphne Evans, 1949 from Himachal Pradesh and its first photographic record from the Western Himalayas (Lepidoptera: Hesperiidae, Pyrginae) - Lovish Garlani (SHILAP, 2022)
The daphne subspecies of Celaenorrhinus ratna Fruhstorfer, [1908] reported first by Evans (1949) from Uttarakhand and has not been reported in the past from the neighbor state Himachal Pradesh. In July 2017, Author recorded and photographed about eight specimens of Celaenorrhinus ratna daphne Evans, 1949 for the first time near McLeodganj town of Himachal Pradesh.